IMPLEMENTATION OF CLOUD COMPUTING ON APPLICATIONS MOBILE JOB INFO - Resha Russita; Hari Toha Hidayat; Safriadi; Muhammad Nasir (PT. Radja Intercontinental Publishing, 2024)
Job vacancy info mobile application has now become an important tool for job seekers in the digital era since the COVID-19 pandemic which recorded a significant spike in the number of unemployed people in Indonesia. In facing this challenge, cloud computing implementation is a crucial solution. This research aims to test performance using the stress testing method and test cloud services from Google Cloud Platform using the Quality of Service (QoS) method. The results show that the server can withstand loads of up to 7000 users simultaneously within 180 seconds or 3 minutes. QoS testing shows that cloud services from Google Cloud Platform achieve an average throughput of 1301.4 kbps with a packet loss rate of 0.54%, an average delay of 0.0019 ms, and an average jitter of 0.00 ms. These results confirm that the implementation of cloud computing in the mobile application of job vacancy information can improve efficiency and quality of service, in accordance with the demands of a dynamic labor market and facing a significant surge in users.